P3 Cognitive Potential in Cochlear Implant Users - Grasel, Signe; Greters, Mario; Goffi-Gomez, Maria Valeria Schimidt; Bittar, Roseli; Weber, Raimar; Oiticica, Jeanne; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2018)
Introduction The P3 cognitive evoked potential is recorded when a subject correctly identifies, evaluates and processes two different auditory stimuli.Objective to evaluate the latency and amplitude of the P3 evoked potential in 26 cochlear implant users with post-lingual deafness with good or poor speech recognition scores as compared with normal hearing subjects matched for age and educational level.Methods In this prospective cohort study, auditory cortical responses were recorded from 26 post-lingual deaf adult cochlear implant users (19 with good and 7 with poor speech recognition scores) and 26 control subjects.Results There was a significant difference in the P3 latency between cochlear implant users with poor speech recognition scores (G-) and their control group (CG) (p = 0.04), and between G- and cochlear implant users with good speech discrimination (G+) (p = 0.01). We found no significant difference in the P3 latency between the CG and G+. In this study, all G- patients had deafness due to meningitis, which suggests that higher auditory function was impaired too.Conclusion Post-lingual deaf adult cochlear implant users in the G- group had prolonged P3 latencies as compared with the CG and the cochlear implant users in the G+ group. The amplitudes were similar between patients and controls. All G- subjects were deaf due to meningitis. These findings suggest that meningitis may have deleterious effects not only on the peripheral auditory system but on the central auditory processing as well.
Keywords: P3 event-related potentials; cochlear implant; speech discrimination